Mr. Lemoncello's fantabulous finale - Grabenstein, Chris (Grabenstein, Chris. Mr. Lemoncello's library, 2024)
Thirteen-year-old Kyle participates in the last of Mr. Lemoncello's fantabulous games with the hopes of winning ownership of the entire Lemoncello empire.